Strategic Combination of DNA-Damaging Agent and PARP Inhibitor Results in Enhanced Cytotoxicity - Horton, Julie K.; Wilson, Samuel H. (Frontiers in Oncology, 2013)
PARP inhibitors (PARPi) are under clinical trial for combination cancer chemotherapy. In the presence of a PARPi, PARP-1 binds DNA strand breaks but cannot produce poly(ADP-ribose) polymers or undergo auto-poly(ADP-ribosyl)ation. DNA binding is persistent, hindering DNA repair. Methylated bases formed as a result of cellular exposure to DNA methylating agents are repaired by DNA polymerase β (pol β)-dependent base excision repair (BER) producing a 5´-deoxyribose phosphate (5´-dRP) repair intermediate. PARP-1 binds and is activated by the 5´-dRP, and PARPi-mediated sensitization to methylating agents is considerable, especially in pol β-deficient cells. Cells deficient in the BER factor XRCC1 are less sensitized by PARPi than are wild-type cells. PARPi sensitization is reduced in cells expressing forms of XRCC1 deficient in interaction with either pol β or PARP-1. In contrast, agents producing oxidative DNA damage and 3´- rather than 5´-repair intermediates are modestly PARPi sensitized. We summarize PARPi experiments in mouse fibroblasts and confirm the importance of the 5´-dRP repair intermediate and functional pol β and XRCC1 proteins. Understanding the chemistry of repair is key to enhancing the clinical success of PARPi.